Untargeted metabolomics analysis identifies creatine, myo‐inositol, and lipid pathway modulation in a murine model of tendinopathy. Issue 4 (17th June 2021) - Sikes, Katie J.; McConnell, Anna; Serkova, Natalie; Cole, Brian; Frisbie, David
Abstract: Tendinopathy has been broadly characterized as alterations in cell proliferation, extracellular matrix turnover/synthesis, and inflammatory alterations. However, the underlying glucose metabolism pathways which contribute to these responses have not been well explored. The potential link between glucose metabolism and tendon pathology is interesting from a global standpoint since the development of spontaneous tendinopathy is associated with systemic metabolic disorders including diabetes mellitus. Therefore, the overarching goal of this study was to understand the potential pathogenic role of glucose metabolism‐driven mechanisms in the development of tendinopathy. To test this, we have utilized an untargeted metabolomics approach to discover pathways which may be altered following tendinopathic injury and treadmill running in an established murine model of TGF‐β1 induced tendinopathy. While specific tendon glucose alterations were not observed via metabolomics or 18 F‐fluoroeoxyglucose (FDG) positron emission tomography/microcomputed tomography imaging ( 18 F‐FDG PET/CT), metabolites including creatinine, D ‐chiro‐inositol, and lipids were dysregulated following tendon injury. As novel pathways for manipulation, the creatine pathway, myo‐inositol pathway, and lipid signaling may lead to the development of enhanced preventative strategies and therapeutic options for all patients who suffer from tendon‐related injuries.